Effects of eucalypt residue management on nutrient leaching and soil properties - Gómez-Rey, M.X. (2013)
Effects of harvest residues on nutrient leaching and soil chemical properties were studied in a lysimeter experiment. Treatments were: (A) forest Xoor litter and harvest residues, other than branches, incorporated into the soil, (B) as A, but with branches cut in 20 cm long bits and placed on the soil surface, (C) as B, but with bits incorporated into the soil, (D) as B, but with branches chopped into chips, (E) as C, but with branches chopped into chips, (F) forest Xoor litter and harvest residues on the soil surface, with branches cut in 20 cm long bits, (G) as F, but with branches chopped into chips, and (H) absence of harvest residues (control). Treatments were applied in zero-tension lysimeters containing 25 kg of soil. Leachates were collected for a 6-year period. At the end of the experiment, lysimeters were dismantled and soil was divided in four layers. Residues, other than branches, increased N leaching, as compared with the control. Branches on the soil surface reduced N leaching when cut in chips. Branches incorporated into the soil reduced leaching independently of their size. Organic residues on the soil surface showed similar effect to those incorporated into the soil. However, harvest residues on the soil surface increased leachate volume, and reduced Ca and P losses. Such a placement of residues led to high contents of Ca and P in the 0–5 cm top soil layer Contents of organic C, total N and base cations were not affected by the treatments.